Ecological and health risk assessment of dissolved heavy metals in the urban road dust. Issue 1 (31st December 2022) - Faisal, Muhammad; Wu, Zening; Wang, Huiliang; Hussain, Zafar; Zhou, Yihong; Wang, Hongfa
ABSTRACT: The purpose of this study was to determine the water-soluble concentrations of hazardous heavy metals in Zhengzhou city road dust in order to quantify the ecological and health risks. It was discovered that Cu (328.3 µg/l), and Zn (191.7 µg/l) were the metals with the highest concentrations, whereas Hg (0.24 µg/l), Cd (2.61 µg/l), and Pb (3.57 µg/l) were the metals with the lowest concentrations of heavy metals. Ecological risk assessment (RI) indicated the most abundant contaminant was Hg, followed by Cu and Cd, while five heavy metals (Cr, Ni, Zn, As, and Pb) fell into the no pollution or low pollution category. Inhalation health risks findings revealed that children were exposed to lead in industrial and commercial environments at levels that were not carcinogenic (HI > 0.1). Children and adults are both exposed to elevated Cu, Pb, and Zn levels in the commercial and residential areas of Zhengzhou.